Some Useful Sources. Issue 1 (8th December 2014) - Hammond, Natalie
Abstract : The references attached to each of the articles offer a wide range of resources for those interested in extending their knowledge of commercial sex policy and literature that takes a socio-cultural approach to sex work more broadly. Additionally, included below are a number of sources that explore commercial sex and sex work policy in their broadest sense. This list is in no sense definitive, but taken with the references in the articles in this themed section, it seeks to demonstrate the spectrum of work that is available.